"Hands-off Labour Forum": The Making and Unmaking of National Working-Class Radio Broadcasting in Canada, 1935-1944 - Klee, Marcus (Labour/Le Travailleur, 1995)
This article examines the Worker Educational Association's National Labour Forum radio series as it developed into a popular, and politically contentious, program with a weekly national audience of 100,000. The series quickly evoked the condemnation of C.D. Howe, head of the powerful Department of Munitions and Supply, and embroiled the program and the WEA in the sectarian struggles of the labour movement. Eventually the WEA was expelled from its central role in the production of Labour Forum and control was transferred to the state's Wartime Information Board and its Committee of Industrial Morale. The Trades and Labour Congress and Canadian Congress of Labour bureaucrats slowly responded to a persistent chorus of protest from workers and union locals, withdrawing their support one year prior to its cancellation in 1944.